Societies’ tightness moderates age differences in perceived justifiability of morally debatable behaviors - Jiang, D.; Li, T.; Hamamura, Takeshi (Springer Verlag, 2015)
Research on age differences in moral judgment tends to focus on children and adolescents. The current study examined age differences in perceived justifiability of morally debatable behaviors across adulthood cross-culturally. A large cross-cultural dataset consisting of 25,142 individuals of varying ages (15–95 years old) from 20 societies was drawn from the World Values Survey. Hierarchical linear modeling was used to test age differences in perceived justifiability of morally debatable behaviors on issues pertaining to honesty and fairness as well as the moderating effect of societies’ tightness. Across societies, older adults judged moral transgression less leniently than did younger adults. However, this pattern was moderated by the societies’ tightness, such that age was a stronger predictor of perceived justifiability of morally debatable behaviors in loose societies relative to tight societies. The current study highlights the importance of examining moral development from the lifespan development perspective. The findings may illuminate potential mechanisms for inter-generational misunderstanding about moral issues.